Effect of Nitrogen Fertilizer on Calcium Oxalate Calibration Density of Porang Bulb (Amorphophallus muelleri Blume) - Bina Rizki Amalia; Nunung Harijati; Retno Mastuti (Natural B, Journal of Health and Environmental Sciences, 2014)
The aim of this research was to know the effects of nitrogen fertilizer to the shape and density of calcium oxalate (CaOx) crystals in porang tuber. Bulbil derived from porang plant in the first growth period seeded until the leaves fully open. Seedlings were transferred to a polybag after most of them has height 50 cm. After adapting for three weeks, the plants were treated with nitrogen fertilizer (urea) with a dose 0, 1, and 5 g/polybag. The plants were grown until the end of the growing period. The slides were prepared by slicing tuber as thin as possible using a sliding microtome. Sliced tuber of porang were cleared by using the modified clearing method. The slides were observed using light microscope to calculate the density of CaOx crystals. The densities of calcium oxalate crystals were analyzed using ANOVA (α = 0,05). The results showed that porang tuber has four kind of crystals i.e. raphide, druse, stiloid, and prism. Nitrogen fertilization had no significant effect on the densities of calcium oxalate crystals.